2001
DOI: 10.1021/jp0109426
|View full text |Cite
|
Sign up to set email alerts
|

Melting and Freezing of Gold Nanoclusters

Abstract: Molecular dynamics simulations were performed on series of gold nanoclusters comprised of 459, 1157, and 3943 atoms, to study their structures and properties during heating and cooling. The increased depression of melting point as particle size decreases has been interpreted in terms of Pawlow's triple point theory, the liquid shell model, and extensions of the two. The solid-liquid interfacial free energy σ sl of ∼0.15 J/m 2 inferred from the liquid shell model was close to the values predicted by several emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
127
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(158 citation statements)
references
References 55 publications
29
127
1
1
Order By: Relevance
“…We can also note that, for the case of the Au 50 Pd 50 particle, previous to the melting transition, the configurational energy drops down slightly due to a geometrical reorganization of the particle to a more energetically favorable structure, as could be noted by the detailed frame-by-frame analysis of the evolution of the structure; a similar behavior was obtained at higher concentrations of palladium. For the Au 100 Pd 0 particle in our simulations, the value of the critical temperature T m is smaller than those obtained by Chushak and Bartell for 459-atom particles 33 and by Nam et al for a 561-atom particle. 34 This discrepancy may be explained by the differences in the models for the atomic interactions but also by the fact that, in both references, the temperature was kept constant, merely forcing the rescaling of the velocities, without the use of a thermostat in the Hamiltonian.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…We can also note that, for the case of the Au 50 Pd 50 particle, previous to the melting transition, the configurational energy drops down slightly due to a geometrical reorganization of the particle to a more energetically favorable structure, as could be noted by the detailed frame-by-frame analysis of the evolution of the structure; a similar behavior was obtained at higher concentrations of palladium. For the Au 100 Pd 0 particle in our simulations, the value of the critical temperature T m is smaller than those obtained by Chushak and Bartell for 459-atom particles 33 and by Nam et al for a 561-atom particle. 34 This discrepancy may be explained by the differences in the models for the atomic interactions but also by the fact that, in both references, the temperature was kept constant, merely forcing the rescaling of the velocities, without the use of a thermostat in the Hamiltonian.…”
Section: Resultscontrasting
confidence: 80%
“…33 In accordance with this, our original cuboctahedral Au 100 structure, relaxed at 300 K, gave a value of Q 6 ) 0.540. However, at higher temperatures, any of these structures will give values of the order parameter smaller than in the perfect array, and, for melted states, the value of Q 6 will drop down to values close to zero.…”
Section: Resultssupporting
confidence: 67%
“…For example, we examined the cluster size effect by using a 561-atom cluster. For this cluster, the formation of the Ih structure is also dominant during freezing, in accordance with previous works [22,26,27]. Further calculations of the free energies of the cluster clearly showed that the low free energy barrier from the liquid to the Ih phase contributes to the dominant formation of the Ih structure during freezing.…”
Section: Figsupporting
confidence: 90%
“…For instance, the Ag-Ni and Ag-Cu nanoparticles are of the core-shell structure with an inner Ni or Cu core and an Ag external shell, 77 and the Cu-Au nanoalloy clusters show an evident compositional dependence of structural characteristic. 78 Aguado et al found that Li and Cs-doped sodium clusters have lower T m than those of pure sodium ones for introducing a chemical defect. 79 However, a single Ni or Cu impurity in Ag icosahedral clusters considerably increases the T m even for sizes of more than a hundred atoms.…”
Section: Thermodynamic Properties Of Alloy Nanoparticlesmentioning
confidence: 99%